2011
DOI: 10.1016/j.nuclphysb.2011.01.032
|View full text |Cite
|
Sign up to set email alerts
|

String-derived MSSM vacua with residual R symmetries

Abstract: Recently it was shown that there is a unique R 4 symmetry for the MSSM which allows the Yukawa couplings and dimension five neutrino mass operator, forbids the µ term and commutes with SO(10). This R 4 symmetry contains matter parity as a subgroup and forbids dimension four and five proton decay operators. We show how to construct string vacua with discrete R symmetries in general and this symmetry in particular, and present an explicit example which exhibits the exact MSSM spectrum, the R 4 symmetry as well a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 56 publications
1
52
0
1
Order By: Relevance
“…On the other hand, AB particles associated with Z I 3 are objects electrically couple toà I µ , thus they are the fundamental strings ending on a, b, c branes in the context of string theory. 10 We choose n 2 a = 0, n 1 c = n 2 d m 3 d , m 3 a = m 3 d = 1, n 1 c = n 2 d = 3 and Ng = 3 in the models studied in [28].…”
Section: Jhep01(2014)049mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, AB particles associated with Z I 3 are objects electrically couple toà I µ , thus they are the fundamental strings ending on a, b, c branes in the context of string theory. 10 We choose n 2 a = 0, n 1 c = n 2 d m 3 d , m 3 a = m 3 d = 1, n 1 c = n 2 d = 3 and Ng = 3 in the models studied in [28].…”
Section: Jhep01(2014)049mentioning
confidence: 99%
“…Various applications have been discussed (see [1][2][3][4][5][6][7][8][9][10][11][12] and references therein) in the contexts of stabilizing baryons, suppressing flavor changing neutral currents and fixing the quark and lepton mixing angles. Recent arguments by Banks and Seiberg shed new light on this subject from a different viewpoint [13].…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in ref [25] we can determine the gauge groups in the hidden sector and this leads to an acceptable gravitino mass in the (multi) TeV-range (provided the dilaton is fixed at a realistic grand unified gauge coupling). If we assume a stabilization of moduli in the spirit discussed in [46,47], we would then remain with a run-away dilaton and a positive vacuum energy. It can be shown that the adjustment of the vacuum energy with a matter superpotential (downlifting the vacuum energy) one can fix the dilaton as well.…”
Section: The Pattern Of Supersymmetry Breakdownmentioning
confidence: 99%
“…Moreover, it has recently been argued that discrete symmetries appear abundantly in string model constructions [15][16][17], with important applications for particle physics model building [18][19][20][21][22]. We are thus in a situation that P 6 could originate from a string model as consistent UV completion and that such a symmetry is compatible with local grand unification.…”
Section: Introductionmentioning
confidence: 99%